A comparative analysis on the physicochemical properties of tick-borne encephalitis virus envelope protein residues that affect its antigenic properties - Bukin, Yu S; Dzhioev, Yu P; Tkachev, S E; Kozlova, I V; Paramonov, A I; Ruzek, D; Qu, Z; Zlobin, V I (Virus research, 2017)
This work is dedicated to the study of the variability of the main antigenic envelope protein E among different strains of tick-borne encephalitis virus at the level of physical and chemical properties of the amino acid residues. E protein variants were extracted from then NCBI database. Four amino acid residues properties in the polypeptide sequences were investigated: the average volume of the amino acid residue in the protein tertiary structure, the number of amino acid residue hydrogen bond donors, the charge of amino acid residue lateral radical and the dipole moment of the amino acid residue. These physico-chemical properties are involved in antigen-antibody interactions. As a result, 103 different variants of the antigenic determinants of the tick-borne encephalitis virus E protein were found, significantly different by physical and chemical properties of the amino acid residues in their structure. This means that some strains among the natural variants of tick-borne encephalitis virus can potentially escape the immune response induced by the standard vaccine.
Keywords: antigeny virové; vazba proteinů; proteiny virového obalu; Encephalitis Viruses, Tick-Borne; chemické jevy; Antigens, Viral; Tick-borne encephalitis virus; Antibody; E protein; Physicochemical properties amino acid residue; Antibodies, Viral; Chemical Phenomena; protilátky virové; Protein Binding; Antigen; Viral Envelope Proteins; Amino Acids; viry klíšťové encefalitidy; aminokyseliny